High-spatiotemporal-resolution distributed Brillouin sensing with transient acoustic wave - Yin Zhou; Yuan Cheng; Jia Ye; Zonglei Li; Haijun He; Wei Pan; Bin Luo; Lianshan Yan (Light: Science & Applications)
Abstract Real-time wide-area environment sensing is crucial for accessing open-world information streams from nature and human society. As a transformative technique distinct from electrical sensors, distributed optical fiber sensing especially for Brillouin scattering-based paradigm has shown superior bandwidth, power, and sensing range. Still, it suffers from insufficient resolution and timeliness to characterize remote dynamic events. Here we develop TABS—a transient acoustic wave-based Brillouin optical time domain analysis sensor, supporting long-range high-spatiotemporal-resolution distributed sensing. By designing a functionally synergistic sensor architecture, TABS elaborately leverages wideband and time-weighted energy transformation properties of a transient acousto-optic interaction to breaking through Brillouin-energy-utilization-efficiency bottleneck, enabling enhancements in overall sensing performance. In the experiment, TABS has achieved a 37-cm spatial resolution over a 50-km range with 1 to 2 orders of magnitude improvement in temporal resolution compared to prevailing Brillouin sensing approaches. For the first time, TABS is explored for state imaging of evacuated-tube maglev transportation system as an exemplary application, showcasing its feasibility and flexibility for potential open-world applications and large-scale intelligent perception.